2020
DOI: 10.1038/s41598-020-71377-0
|View full text |Cite
|
Sign up to set email alerts
|

Testicular blood supply is altered in the 41,XXY* Klinefelter syndrome mouse model

Abstract: Hypergonadotropic hypogonadism is a major feature of Klinefelter syndrome (KS), assumed to be caused by testicular hormone resistance. It was previously shown that intratesticular testosterone levels in vivo and Leydig cell function in vitro seem to be normal indicating other functional constraints. We hypothesized that impaired testicular vascularization/blood flow could be a co-factor to the observed hypergonadotropic hypogonadism. We evaluated the testicular vascular system by measuring blood vessel sizes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Moreover, the KEGG analysis revealed genes involved in steroidogenesis pathogenesis to be up-regulated in the KS samples, which is in accordance with research showing an increased intratesticular testosterone level in KS men (44). Although no changes in the blood vessel density were found in KS testicular biopsies compared to controls, as reported in our previous research (25), the above nding may contribute to the hypothesis that a disturbed vascularization is present within the KS testis (45,46). In KS men, as in females, one of the two X-chromosomes is silenced to compensate for the dosage of X-linked genes.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the KEGG analysis revealed genes involved in steroidogenesis pathogenesis to be up-regulated in the KS samples, which is in accordance with research showing an increased intratesticular testosterone level in KS men (44). Although no changes in the blood vessel density were found in KS testicular biopsies compared to controls, as reported in our previous research (25), the above nding may contribute to the hypothesis that a disturbed vascularization is present within the KS testis (45,46). In KS men, as in females, one of the two X-chromosomes is silenced to compensate for the dosage of X-linked genes.…”
Section: Discussionsupporting
confidence: 89%
“…The histological finding of a low blood vessel/testis surface ratio in a mouse model of KS led to the hypothesis that T release, rather than its production, is actually impaired in KS, by means 271 of a slower and reduced testicular blood flow. These results were confirmed in a subsequent 272 study, in which a reduction in small and medium-sized blood vessels in adult 41,XX Y * mice was described, and the CEUS study of those testes demonstrated reduced perfusion parameters, favoring impaired testicular vascularization in KS (14). However, these results were inconsistent with the findings of another histological study in human KS testicular biopsies from prepubertal, peripubertal, and adult subjects (15).…”
Section: Discussionmentioning
confidence: 73%
“…The present study examined for the first time in vivo testicular vascularization in human subjects with KS by means of CEUS compared with age-matched controls. Subjects with KS were characterized by significantly slower testicular perfusion kinetics, in both the wash-in and washout phases (Figure 2), resulting in prolonged testicular MTT; the testicular Slopein was not significantly different between the two groups, possibly because of the lack of differences in the number of larger arteries (14), in which microbubbles first appear; the PI and AUC were also not different between the two groups. Strikingly, faster testicular vascularization times were associated with better endocrine testicular function, especially with serum T levels, which showed a strong relationship with vascular parameters, correlating positively with Slopein and inversely with Tin, MTT, TTP, and 287 Tout.50% as well as gonadotropins and T/LH and cfT/LH ratios.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations